The molecular characteristics, diagnosis, and treatment of macrolide-resistant Mycoplasma pneumoniae in children - Leng, Maodong; Yang, Junmei; Zhou, Juanjuan (Frontiers in Pediatrics, 2023)
The purpose of this study is to review the molecular characteristics, the diagnosis and treatment of the widespread infection of macrolide-resistant Mycoplasma pneumoniae (M. pneumoniae and MRMP) in children, thus providing a better knowledge of this infection and presenting the associated problems. Single point mutations in the Ⅴ region of the 23S rRNA gene of M. pneumoniae genome are associated with macrolide resistance. P1-1, MLVA4-5-7-2, and ST3 are usually the predominated genetic types in the M. pneumoniae epidemics. The short-term 2 times serological IgM (or together with IgG) test in the acute stage can be used for confirmation test. Combined serological testing and PCR might be a more prudent method to reduce macrolide consumption and antibiotic selective pressure in clinical setting. Molecular methods for the detection of single nucleotide mutations in the Ⅴ region of the 23S rRNA gene can be used for the diagnosis of MRMP. The routine use of macrolide for the treatment of macrolide-resistant Mycoplasma pneumoniae (MSMP) infections can get good effect, but the effects are limited for severe MRMP infections. Additional corticosteroids may be required for the treatment of severe MRMP infections in children of China during the era of MRMP.